Finite element analysis applications : a systematic and practical approach / Zhuming Bi - Bi, Zhuming
Finite Element Analysis Applications: A Systematic and Practical Approach strikes a solid balance between more traditional FEA textbooks that focus primarily on theory, and the software specific guidebooks that help teach students and professionals how to use particular FEA software packages without providing the theoretical foundation. In this new textbook, Professor Bi condenses the introduction of theories and focuses mainly on essentials that students need to understand FEA models. The book is organized to be application-oriented, covering FEA modeling theory and skills directly associated with activities involved in design processes.